2014
DOI: 10.1097/iae.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Area of Peripheral Retinal Nonperfusion and Treatment Response in Branch and Central Retinal Vein Occlusion

Abstract: The area of peripheral retinal nonperfusion is variable in patients with retinal vein occlusion and affects its clinical course and response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 18 publications
2
90
1
3
Order By: Relevance
“…The ultra wide-field imaging has a shorter image capture time and allows visualisation of significantly larger areas of the retina using less number of images compared to the conventional 7-field imaging. For example, the ultra wide-field image obtained by Optos Plc, Dumfermline, Scotland, United Kingdom covers approximately a 200 degree field of view in a single image compared to the 30 to 50 degree conventional fundus cameras and is now regularly used in clinical practice [3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultra wide-field imaging has a shorter image capture time and allows visualisation of significantly larger areas of the retina using less number of images compared to the conventional 7-field imaging. For example, the ultra wide-field image obtained by Optos Plc, Dumfermline, Scotland, United Kingdom covers approximately a 200 degree field of view in a single image compared to the 30 to 50 degree conventional fundus cameras and is now regularly used in clinical practice [3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of ultra wide-field imaging, an ischemic index method has been developed to quantity non-perfusion by taking into account the much larger retinal area visualized 3 . In brief, the ischemic index method is measured as a perfused ratio or percentage of the total area of perfused retina to the total area assessed by manually delineating the boundaries of the retina that are in focus and also the perfused retina [3][4][5][6][7] . Other investigators have quantified the total area of non-perfusion by manually or software assisted delineation of the non-perfused boundaries without taking into account the total area visualized and reported the area of non-perfusion in pixels or as total disc areas 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to correlate directly with the presence of neovascularization, as well as the degree of macular edema and response to antivascular endothelial growth factor (anti-VEGF) treatment. 20 While the ischemic index has been helpful in the context of research analysis of wide-field angiograms, it has not found its way into the everyday practice of the typical retinal physician. In addition to visualizing the peripheral retina, ultra-wide-field imaging has been shown to accurately demonstrate macular edema and the foveal avascular zone, as measured against spectral domain OCT. 21,22 While cystoid macular edema secondary to retinal vein occlusions is classically treated with anti-VEGF injections, one case report demonstrates that wide-field guided assessment of retinal nonperfusion and corresponding TRP may break the cycle of rebound edema that often occurs when anti-VEGF injections are stopped.…”
Section: Retinal Vein Occlusionmentioning
confidence: 99%
“…[8][9][10][11] It has also been evaluated extensively in a spectrum of other retinal diseases, particularly retinal vasculopathies. 12,13 These studies have contributed to the growing significance of peripheral findings to disease management. The ease and speed of optomap image capture makes it feasible to incorporate them into routine exams with the result that overall exam time is reduced and patient satisfaction increased.…”
mentioning
confidence: 99%